Classical Islamic Sciences and Contemporary Academia: Efforts to Bridge the Intellectual Heritage - Abdul Jabbar Sarabioda; Mohd Gufran Barkati; Mohammad Tabish (International Journal of Islamic Teaching and Learning, 2025)
The revival of classical Islamic sciences in modern academia represented a profound opportunity to bridge the gap between traditional knowledge systems and contemporary educational frameworks. Their integration into modern academia enhanced multidisciplinary research, fostered ethical paradigms, and cultivated global citizenship grounded in spirituality and intellectual rigor. This paper analyzed the theoretical underpinnings of the classical sciences in Islam, their historical significance, and their relevance in addressing contemporary issues. This study employed a qualitative method with a content analysis approach, utilizing books, articles, theses, and other relevant documents as data sources. The collected data were analyzed thematically to identify key patterns and insights. The findings indicate that modern academia can benefit from classical Islamic sciences by embracing the principles of interdisciplinary and collaboration to address the multifaceted challenges of the 21st century. These insights contribute to strengthening the role of Islamic intellectual heritage in contemporary academic discourse and educational development.